Efisiensi Presensi Guru melalui Implementasi Sistem Android dengan Metode Agile Scrum - Nugroho, Rizky Ageng; Bahtiar, Arief Rais (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to design and develop an Android-based teacher attendance system using the Agile Scrum method to address the issues of manual attendance at SMP Negeri Satu Atap 1 Bantarsari. The current manual system is vulnerable to fraud such as data manipulation, data loss, inaccurate recapitulation, and requires up to two hours to complete, in addition to causing long queues for teachers. The Agile Scrum method was chosen for its flexibility and well-structured software development process. The research process involved several stages, beginning with a needs analysis to understand user specifications and expectations. Next, system design was carried out using Unified Modeling Language (UML), followed by application implementation and testing with Black Box Testing. The results show that the application successfully improved attendance efficiency from 42.1% to 78.9%, with features such as multi-user login, attendance recording, data recapitulation, and teacher data management by the administrator. Data security is ensured through Firebase integration. This application is expected to enhance teacher productivity and work discipline, while serving as an example of modern technology adoption in the educational environment